Critical evaluation of KCNJ3 gene product detection in human breast cancer: mRNA in situ hybridisation is superior to immunohistochemistry. Issue 12 (3rd October 2016) - Kammerer, Sarah; Jahn, Stephan Wenzel; Winter, Elke; Eidenhammer, Sylvia; Rezania, Simin; Regitnig, Peter; Pichler, Martin; Schreibmayer, Wolfgang; Bauernhofer, Thomas
Abstract : Increased expression levels of KCNJ3 have been correlated with lymph node metastases and poor prognosis in patients with breast cancer, suggesting a prognostic role of KCNJ3 . We aimed to establish protocols for the detection of KCNJ3 in formalin-fixed, paraffin-embedded (FFPE) breast cancer tissue. Several antibodies were tested for sensitivity and specificity by western blot, followed by optimisation of the immunohistochemistry (IHC) procedure and establishment of KCNJ3 mRNA in situ hybridisation (ISH). Methods were validated by processing 15 FFPE breast cancer samples for which microarray data were available. Spearman's rank correlation analysis resulted in borderline significant correlation for IHC versus ISH ( rS : 0.625; p <0.05) and IHC versus microarray ( rS : 0.668; p <0.01), but in significant correlation for ISH versus microarray ( rS : 0.861; p <0.001). The ISH method was superior to IHC, regarding robustness, sensitivity and specificity and will aid to further study expression levels of KCNJ3 in both malignant and physiological conditions.